Energy efficient glazing: A comparison of microalgae photobioreactor and Iranian Orosi window designs. (1st April 2023) - Ahmadi, Ferial; Wilkinson, Sara; Rezazadeh, Hamidreza; Keawsawasvong, Suraparb; Najafi, Qodsiye; Masoumi, Arash
Abstract: Orosi is a traditional Iranian window which is made of colorful glasses embedded in wooden latticed frame. This window was designed in traditional courtyard houses located in central Iran and behaved as a passive strategy to control light intensity, provide privacy and aesthetics. However, this type of window is rarely used nowadays due to a lack of acoustic and thermal insulation and high construction costs. This paper explores the possibility of using double-glazed window with colored microalgae inspired by Orosi to improve its light performance and energy consumption compared to the traditional Orosi window design A series of experimental tests and a set of computer simulations are conducted to evaluate and compare the two designs. The experimental results showed that while the light intensity in the indoor space is approximately equal to the corresponding magnitude measured for the Orosi window, the inside temperature witnessed a small increase approximately 1° Celsuis. Likewise, relative humidity, which has a significant impact on thermal comfort perceived by occupants, increased from 25% to nearly 70% in the algae window. Based on results obtained, nearly 500 ppm of CO2 was absorbed due to the low height of the photobioreactor. Results of computer simulations indicated that the amount of annual energy consumption in terms of cooling electric energy, heating fuel energy and electric equipment within the two simulated models were similar. However, the best performance of the colored algae window in terms of UDI was observed when the microalgae concentration was between 40% and 50%. Highlights: For the first time, a colored microalgae window inspired by Iranian Orosi is evaluated as an energy efficient design. Using this window could result in reviving Iranian architecture and absorb CO2 emissions and decrease energy consumption. Indoor lux levels are found to be very similar for both designs. Indoor temperature and RH value of the double-glazed algae photobioreactor window was higher. Energy consumption for heating and cooling were similar for both window designs.